Surface chemical bonds, surface-enhanced Raman scattering, and dielectric constant of SiO2 nanospheres in-situ decorated with Ag-nanoparticles by electron-irradiation - Phatangare, A. B.; Dhole, S. D.; Dahiwale, S. S.; Mathe, V. L.; Bhoraskar, S. V.; Late, Dattatray J.; Bhoraskar, V. N. (Journal of Applied Physics, 2016)
Nanostructures of dielectric materials decorated with metal nanoparticles are of great scientific interest; however, the involved synthesis methods are complicated and require multistep chemical processing, including functionalization of the dielectric surfaces. In the present work, without chemical processes, silver nanoparticles of average sizes in the range of 11 to 15 nm were in-situ synthesized and decorated on SiO2 nanospheres in a single step process by irradiating a solution (AgNO3-polyvinylpyrrolidone (PVP)-SiO2 nanospheres) with 6 MeV electrons at 1.5 x 10(15) e(-)/cm(2), 3.0 x 10(15) e(-)/cm(2), and 4.5 x 10(15) e(-)/cm(2) fluences. The electron irradiated solutions were characterized with different surface and other techniques. The results revealed that the SiO2 nanospheres were uniformly decorated with Ag nanoparticles, and the prominent chemical bonds involved were Ag-O, Si-O-Ag, and Si-Ag. Moreover, the sizes and the decoration density of Ag nanoparticles could be tailored by varying electron fluence. The Surface-enhanced Raman scattering (SERS) of 4-aminothiophenol (4-ATP) solutions was studied using substrates in the form of thin coatings of the solutions of Ag-decorated SiO2 nanospheres. The appearance of the characteristic SERS peaks of both 4-ATP and 4, 4'-dimercaptoazobenzene (4, 4'-DMAB) in Raman spectra confirmed the conversion of a fraction of 4-ATP into 4, 4'-DMAB in the presence of Ag nanoparticles. Composites in the form of thin films were synthesized from the mixture solutions of PVP and Ag-decorated SiO2 nanospheres. The dielectric constant of each thin film was higher as compared to polymers, and could be tailored by varying electron fluence used for decorating Ag nanoparticles. Published by AIP Publishing.